Kajian Penerimaan Teknologi Digitalisasi Bagi Mahasiswa Jurusan Ilmu Perpustakaan UIN Syarif Hidayatullah Jakarta - Ade Abdul Hak (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2016)
This study investigated the implementation of "Scan Snap SV600 + Rack2-Filer" – as a digitalization technology- in the Library of Adab Faculty, UIN Syarif Hidayatullah Jakarta. It is important to know the effectiveness of the technology as one of learning materials. The lecture was held by students of Library Department, UIN Syarif Hidayatullah Jakarta, in the second semester. It was involved 97 students from three classes in 2015. The approach used in this research was TAM model that was based on the variables of perceived ease of use (PEOU), perceived usefulness (PU), attitude toward behavior (ATU), and behavioral intention (BI). Questionaires collected with the saturated approach were analysed using SPSS version 22. The result showed that the mean score for all of the variables was very high out of maximum score obtainable of 4. T-Test analysis indicated that there was positive and significant effect for some variables, except the perceived usefulness (PU) to the behavioral intention (BI) with effect value of 0,051; and the attitude toward behavior (ATU) to behavioral intention (BI) with effect value of 0,193 . Meanwhile, the most occurred in the perceived ease of use (PEOU) to the perceived usefulness (PU) with effect value of 0,332%. Thus, the easiness becomes higher than usefulness in using the technology for students. So, there is something more important to teach how the students take the technology in the perceived usefulness than the perceived ease of use.